Accelerated single cell seeding in relapsed multiple myeloma - Heather J. Landau; Venkata Yellapantula; Benjamin T. Diamond; Even H. Rustad; Kylee H. Maclachlan; Gunes Gundem; Juan Medina-Martinez; Juan Arango Ossa; Max F. Levine; Yangyu Zhou; Rajya Kappagantula; Priscilla Baez; et al. (Nature Communications, 2020)
In multiple myeloma, disease progresses via seeding to different anatomic sites and clonal expansion. Here, utilising autopsy material, the authors show that systemic seeding accelerates at relapse following treatment.